Insurgency in Northeast India: A Stumbling Block for India’s tie with South East Asia in the Way of Development - Bala, Dr. Rajni (The journal of contemporary issues in business and government, 2019)
Insurgency is one of the important impediments to India‘s relations with South East Asian countries in the way of development. India had a good tie with Southeast Asian countries before the advent of British. The term ‗Indo-China‘ in this region is the glaring example of it. The term ‗Indo-China‘ here does not mean India and China; it represents a particular region in the South East Asia i.e. Laos, Cambodia and Vietnam because that region was under the influence of India and China in a certain period of time. This region (South East Asia) is very significant, because the Indian National Army (INA) was founded on 21 October, 1943mainly by Indian prisoners of war in Singapore. Then the INA under the leadership of Netaji Subhas Chandra Bose attacked the British with the help of Japanese forces for the liberation of India during the Second World War period and proceeded up to Kohima, Nagaland. On 14th April, 1944, Col. Shaukat Hayat Malik , Commanderof Bahadur Group of INA hoisted India‘s national flag (tri-color) on Indian soil (mainland) first time at Moirang, Manipur with the help of Manipuris like MairenbamKoireng Singh and others who were the members of INA.